Global inactivation of carboxylesterase 1 (Ces1/Ces1g) protects against atherosclerosis in Ldlr(−/−) mice - Xu, Jiesi (Sci Rep, 2017)
Atherosclerotic cardiovascular disease is a leading cause of death in the western world. Increased plasma triglyceride and cholesterol levels are major risk factors for this disease. Carboxylesterase 1 (Ces1/Ces1g) has been shown to play a role in metabolic control. So far, the role of mouse Ces1/Ces1g deficiency in atherosclerosis is not elucidated. We generated Ces1/Ces1g (−/−) mice. Compared to wild-type mice, Ces1/Ces1g (−/−) mice had reduced plasma cholesterol levels. We then generated Ces1g (−/−) Ldlr (−/−) double knockout (DKO) mice, which were fed a Western diet for 16 weeks. Compared to Ldlr (−/−) mice, DKO mice displayed decreased plasma cholesterol and TG levels and reduced atherosclerotic lesions. Interestingly, knockdown of hepatic Ces1/Ces1g in Apoe (−/−) mice resulted in hyperlipidemia and exacerbated Western diet-induced atherogenesis. Mechanistically, global inactivation of Ces1/Ces1g inhibited intestinal cholesterol and fat absorption and Niemann-Pick C1 like 1 expression, and increased macrophage cholesterol efflux by inducing ATP-binding cassette subfamily A member 1 (ABCA1) and ABCG1. Ces1/Ces1g ablation also promoted M2 macrophage polarization and induced hepatic cholesterol 7α-hydroxylase and sterol 12α-hydroxylase expression. In conclusion, global loss of Ces1/Ces1g protects against the development of atherosclerosis by inhibiting intestinal cholesterol and triglyceride absorption and promoting macrophage cholesterol efflux.